A review of dynamic voltage support for power grids with large-scale penetration of renewable generation - Song Gao; Haifeng Zhang; Xiangdong Meng; Yifu Zhang (Frontiers in Energy Research)
Dynamic voltage stability analysis and control of power systems with large-scale penetration of renewable energy have gained significant attention in relevant fields. This article provides the latest development of dynamic voltage support technology under such a scenario, covering the following four main aspects. Firstly, the mechanism and challenges of dynamic voltage analysis with the development of large-scale renewable energy are described, and the state-of-the-art status and problems of dynamic voltage support are discussed. Second, the aggregation modeling method suitable for dynamic voltage support of both photovoltaic (PV) and wind farms is analyzed, considering the dynamic voltage response characteristics and control technologies. Then, the innovation of multi-types reactive power sources coordinated control based on autonomous decentralized control and its realization are discussed. Finally, the key problems of dynamic voltage support technology to be solved in the renewable energy-penetrated power grids are described, and the future research and development work is outlined.